Brazilian Consumers' Preference towards Pork - Machado, Sivanilza Teixeira [UNESP]; Naeaes, Irenilza de Alencar [UNESP]; Mendes dos Reis, Joao Gilberto [UNESP]; Vendrametto, Oduvaldo [UNESP]; Grabot, B.; Vallespir, B.; Gomes, S.; Bouras, A.; Kiritsis, D. (Springer, 2014)
Brazilian pork supply chain has various challenges reflected by the consumers' preference perception, which is one of the lowest in the Western world. Several researches have shown that there is a divergence between consumer preferences and actual pork consumption. This study aimed to examine the Brazilian consumers' preference towards pork. An online survey was developed in order to investigate the marketing of pork at the retailer level. Analytic Hierarchy Process (AHP) was applied in order to classify the consumers' alternatives related to the frequency of eating pork, which were weekly, biweekly and monthly consumption. Results showed that the factors that most contribute to the purchase decision of pork are household income, commodity price and the characteristics related to meat quality.
Keywords: Food; Consumers preferences; Market; Brazil